Evaluation of the key prescription sequence symmetry analysis assumption using the calcium channel blocker: Loop diuretic prescribing cascade. Issue 1 (6th October 2021) - Vouri, Scott M.; Morris, Earl J.; Usmani, Silken A.; Reise, Rachel; Jiang, Xinyi; Pepine, Carl J.; Manini, Todd M.; Malone, Daniel C.; Winterstein, Almut G.
Abstract: Objectives: To evaluate the prescription sequence symmetry analysis assumption regarding balance between marker drug (i.e., medication used to treat a drug‐induced adverse event) initiation rates before and after initiation of an index drug (i.e., medication that is potentially associated with the drug‐induced adverse event) in the absence of prescribing cascades, we used a well‐described example of loop diuretic initiation to treat dihydropyridine calcium channel blockers (DH CCB)‐induced edema. Study design and setting: The University of Florida Health Integrated Data Repository from June 2011 and July 2018 was used to assess temporal prescribing of DH CCB and loop diuretics within the prescription sequence symmetry analysis framework. Validation of the prescribing cascade was performed via clinical expert chart review. Results: Among patients without heart failure who were initiated on DH CCB, 26 and 64 loop diuretics initiators started within 360 days before versus after DH CCB initiation, respectively, resulting in an adjusted sequence ratio (aSR) of 2.27 (95% CI, 1.44–3.58). Overall, 35 (54.7%) patients were determined to have a prescribing cascade. Removing patients who experienced a prescribing cascade resulted in an aSR of 1.05, 95% CI 0.62–1.78). Conclusion: Loop diuretic initiation rates before and after DH CCB initiation for reasons other a prescribing cascade were similar, thus confirming the prescription sequence symmetry analysis assumption.